Gender differences in educational attainment: evidence on the role of the tracking age from a Finnish quasi-experiment - Tuomas Pekkarinen (Institute for the Study of Labor (IZA), 2005)
This paper studies the relationship between the timing of tracking of pupils into vocational and academic secondary education and gender differences in educational attainment and income. We argue that in a system that streams students into vocational and academic tracks relatively late (age 15-16), girls are more likely to choose the academic track than boys because of gender differences in the timing of puberty. We exploit the Finnish comprehensive school reform of the 1970's to analyze this hypothesis. This reform postponed the tracking of students from the age of 10-11 to 15-16 and was adopted gradually by municipalities so that we can observe members of the same cohorts in both systems. We find that the postponement of the tracking age increased gender differences in the probability of choosing the academic secondary education and in the probability of continuing into academic tertiary education. The reform had particularily negative effects on boys from non-academic family backgrounds. Finally, the reform decreased the gender wage gap in adult income by four percentage points.
Keywords: I20; J16; 330; education; tracking; gender wage gap